Efektifitas Pertanggungjawaban Hukum Pidana Terhadap Pemalsuan Dokumen atas Objek Tanah yang telah Dialihkan (Putusan No. 634/Pid.B/2020/PN Mks) - Alfiani, Andi Nurafni Ayu; Khalid, Hasbuddin; Hambali, Azwad Rachmat (Innovative: Journal Of Social Science Research, 2025)
Abstract This research aims to examine the judge’s legal considerations in establishing criminal liability for document forgery involving land that has already been transferred, as well as to assess the extent to which criminal sanctions reflect substantive justice. The object of study is Decision Number 634/Pid.B/2020/PN Mks, which involved the defendant Samudin bin Dg. Bora, who was found guilty of using a falsified deed of sale to regain control over previously transferred land and resell it. An empirical legal approach was employed, using interviews with a judge at the Makassar District Court and members of the public familiar with the issue of document forgery in land transactions. The findings reveal that the judge’s considerations in the aforementioned decision were based on the fulfillment of the elements of Article 263 paragraph (2) of the Indonesian Criminal Code, with the defendant legally and convincingly proven guilty. The verdict, upheld at both appellate and cassation levels, reflects procedural consistency in the application of criminal liability. However, the effectiveness of the criminal justice system in this case appears to be more procedural than substantive. Interviews indicate that the public has not fully experienced tangible legal protection, as document forgery in land disputes remains prevalent and lacks structural preventive measures. This highlights a gap between formal legal outcomes and the realization of justice within the broader community. This study recommends strengthening a criminal law approach that not only emphasizes punishment but also includes more substantive preventive efforts and broader access to legal protection for the public in addressing document forgery in land affairs. Keywords: Document Forgery, Land Ownership, Criminal Liability, Substantive Effectiveness, Case Study, Public Perception